A review: The utilization of Indigofera Zollingeriana as animal feed additional supplements - Ali Zainal-Abidin, Mohamad Termizi; Abdul Syukor, Abd Razak; Muhammad Amirul Syafiq, Nasarudin; Nurul Farah Anisa, Hairolnizam; Farah Amalina, Ishak; Suryati, Sulaiman; Mohd Rashid, Ab Hamid; Noraini, Samat (Penerbit UMP, 2024)
This review explores the possibility of Indigofera Zollingeriana as an animal feed supplement. With the increasing price of the ingredients for animal feed, we need to find alternative food source for the livestock. It examines the environmental and economic considerations of cultivating this plant specifically for animal consumption. Additionally, the review delves into the potential nutritional value of Indigofera Zollingeriana, assessing its suitability as a feed supplement to enhance animal health and productivity. The core focus lies in determining the feasibility of incorporating Indigofera Zollingeriana into animal feed production systems in a way that is both environmentally responsible and economically viable. By evaluating its potential as a sustainable feed source, this review contributes to the ongoing search for innovative and eco-friendly solutions to meet the growing demand for animal feed to solve the food security issues.